'Pentik' - Richard, Anak Bandar. (unimas, 2004)
Pentik' is a wooden Than sculpture that resembles the human figure which is believed to have supernatural and spiritual powers. The beliefs of animism among the indigenous Iban group also displays the activities roles of `Pentik' in social such as hunting, medication, burial ceremony and traditional agriculture. I studied `Pentik' from various aspects such as its uniqueness, beauty and culture significance. I used bulbs of various colors for its eyes. The blinks from the flashes of light represents the energy and spiritual powers. I used bulbs different shapes, sizes and colors to create the distinctive features that differs from the original `Pentik'.